Design and Performance Analysis of Body Wearable Antenna - Singh, Jaget; Sohi, B.S (International Journal of Computer Sciences and Engineering, 2025)
In this paper an inset feed, rectangular microstrip textile patch antenna operating at 2.4 GHz has been proposed. The designed antenna is analyzed under bend and normal condition. For design of this antenna, 2.85 mm thick polyester fabric with dielectric constant of 1.44 is used as a substrate and 0.04 mm thick copper is used as conductive part of antenna. The designed antenna is tuned at desired frequency with return loss of -32.5 dB and an impedance bandwidth of 90 MHz is observed. Then same antenna is simulated on a three layer body phantom model (containing properties of muscles, skin and fat) for flat and bending conditions. A SAR (specific absorption rate) analysis is also done on the basis of 1 g and 10 g tissue of human body. Variations in performance parameters like return loss, gain and SAR due to lossy nature of human body are observed and analyzed. Further EBG (electromagnetic band gap) material is used to reduce SAR